2021
DOI: 10.3390/jcm10020356
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Role of Pericardial Fat as a Biomarker Connected to Coronary Calcification—A Deep Learning Based Approach Using Fully Automated Body Composition Analysis

Abstract: (1) Background: Epi- and Paracardial Adipose Tissue (EAT, PAT) have been spotlighted as important biomarkers in cardiological assessment in recent years. Since biomarker quantification is an increasingly important method for clinical use, we wanted to examine fully automated EAT and PAT quantification for possible use in cardiovascular risk stratification. (2) Methods: 966 patients with intermediate Framingham risk scores for Coronary Artery Disease referred for coronary calcium scans were included in clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 35 publications
(65 reference statements)
1
20
0
4
Order By: Relevance
“… 10 Similar to our results that showed that an increase in M2 macrophage density was correlated with an increase in plaque size and calcification, other imaging studies found an association between PvAT volume and coronary artery calcification. 25 , 26 , 27 Moreover, macrophage infiltration and neoangiogenesis in the epicardial adipose tissue were associated with mild coronary calcification; however, macrophage polarization was not assessed. 28 In atherosclerotic plaques, M2 macrophages seem to play a role in inflammation resolution through macrocalcification.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Similar to our results that showed that an increase in M2 macrophage density was correlated with an increase in plaque size and calcification, other imaging studies found an association between PvAT volume and coronary artery calcification. 25 , 26 , 27 Moreover, macrophage infiltration and neoangiogenesis in the epicardial adipose tissue were associated with mild coronary calcification; however, macrophage polarization was not assessed. 28 In atherosclerotic plaques, M2 macrophages seem to play a role in inflammation resolution through macrocalcification.…”
Section: Discussionmentioning
confidence: 99%
“…Additional determination of PAT might, therefore, be a useful tool to improve risk stratification in particular, as PAT volume can be assessed easily from data sets acquired for calcium screening. It has already been shown before that PAT combined with CAC might improve risk stratification for future cardiovascular events [ 20 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…No cut-off scores were identified in EAT and pericardial adipose tissue features for high-risk coronary artery disease (46).…”
Section: Ai: Epicardial and Pericardial Adipose Tissuesmentioning
confidence: 99%
“…Kroll et al examined a method for fully automatic quantification of epicardial and paracardial adipose tissues for possible use in cardiovascular risk assessment (46). A deep learning network was used for quantification of adipose tissue from coronary CT in 966 patients with intermediate Framingham risk scores.…”
Section: Ai: Epicardial and Pericardial Adipose Tissuesmentioning
confidence: 99%